Early specialization in youth hockey: a parental perspective - Ruest, J. (University of Ottawa, 2020)
Early sport specialization is a phenomenon that continues to be practiced in today`s youth sports environment. The purpose of this study was to explore practices around early specialization within the minor hockey context in Eastern Ontario. More specifically, the goal of this thesis was to better understand parental perspectives on specialization versus diversification relative to their child`s experience in the sport of ice hockey. Additionally, this study aimed to uncover the rates of specialization in Minor Peewee AA ice hockey players in Eastern Ontario and the factors that influence those who specialize. A concurrent embedded mixed-methods procedure was employed for this study; a total of 114 survey responses and 15 semi-structured interviews formed the study sample. Findings in the study reveal a large majority of parents foster specialization in their child as 87% (n=114) of survey participants identified as having a child who specializes in the sport of ice hockey. However, interview data revealed that parents favor development through diversification. Individual influences such as parents and coaching staff were found to be contributing factors to the phenomenon of specialization. Further, the availability of resources within the hockey context was additionally found to influence specialization. Finally, Hockey Canada`s current position was cogitated with the results to reveal a strong inclination towards elite development. Results indicate a need for parent and coach education regarding their role in early specialization and their support for diversification of sport experiences. It is of particular importance during the transitioning years in particular where stakeholders (parents, coaches, administration) foster the sense of well-rounded development of a participating child not just for the preparation for the elite stages of sport but for overall wellness of the individual.